Reduction of postoperative pain after infiltration of local anesthetic at the port site and subdiaphragmatic space in laparoscopic cholecystectomy: A cross-sectional study - Bhattarai, Sameer; Pyakurel, Kumud; Nalbo, Dinesh; Khanal, Kanak; Pandit, Narendra (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Port site and subdiaphragmatic infiltration of local anesthetics during laparoscopic cholecystectomy (LC) is preferred by surgeons to decrease postoperative pain. LC with local anesthetics infiltration as well as without any local anesthetic both have been standard surgical practice. However, the difference in the reduction of postoperative pain in these two groups is not well known. The objective of the study was to compare the postoperative pain with and without infiltration of local anesthetic at the port site and subdiaphragmatic space in LC. Methods: A hospital-based cross-sectional study was conducted from 25 April 2021 to 25 October 2021 among 60 patients who underwent elective LC. The patients were divided into two equal groups. The study group received infiltration of 20 ml of bupivacaine (0.5%) at the port site and the subdiaphragmatic space, while the control group did not receive any local anesthetic. The primary outcome measure was the visual analog pain score at 6, 12, 24 and 48hrs postoperatively. Results: Among 60 patients, the majority were female- 40(66.7%); and 40-50 years age group. The two groups were comparable in terms of age, sex, ASA, BMI and duration of pneumoperitoneum and surgery. Infiltration of a local anesthetic agent produced effective postoperative analgesia in the immediate postoperative hours (6, 12 and 24 hours) and was found to be statistically significant when compared to the no-local anesthesia group. Conclusion: The intraoperative port site and subdiaphragmatic local infiltration is effective at reducing postoperative pain in the first 12 hours without any adverse events.